DESAIN LKPD BERORIENTASI KOMPLEKSITAS KONTEN DAN PROSES KOGNITIF PADA MATERI CAHAYA DAN ALAT-ALAT OPTIK UNTUK PEMBELAJARAN FISIKA SMA/MA - Mia Cahyanti; Amali Putra; Letmi Dwiridal (Universitas Negeri Padang, 2017)
This research was motivated by the demands of 2013’s curriculum toward the dimensions of knowledge which taught in physics learning and and the levels of cognitive processing which should be trained in learning. Instructional materials and student worksheet (LKPD) used generally do not contain the four dimensions of knowledge and have not been trained the six levels cognitive processes according to Bloom's revision taxonomy. Based on the preliminary study result was known that the competence level of knowledge’s students in cognitive processes C4, C5, and C6 were still very low. One of the solutions is to use LKPD oriented to content complexity and cognitive processes. The purpose of this study was to produce a LKPD content complexity and cognitive processes which are valid, practical, and effective for physics learning in SMA/MA. Research conducted included the type of Research and Development (R&D) using the 4D models development which was reduced into 3D, so this study consist of three stages, which are define, design, and develop. LKPD trials conducted with one group pretest-posttest design. Subjects of research consist of 5 validators (three lecturers of Physics, and 2 Physics teachers SMAN 4 Padang), 3 Physics teachers tested the practicality of LKPD, and eleventh grade students of MIPA1 SMAN 4 Padang. The results of the research showed the LKPD is very valid and very practical, the validity of rate is 3.77 (expressed in percent 94.5%) then the practicality rate based on teachers’ opinion is 3.81 (expressed in percent 95%), and practicality rate based on students’ opinion is 3.57 (expressed in percent 89.25%). The LKPD on learning material of Light and Optical Instrument showed increased understanding with n-gain of 0.53 on medium category. LKPD can enhance high order thinking capabilities of students in Light and Optical instrument materials